2016
DOI: 10.1108/et-06-2015-0042
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cooperative education and reflection upon previous work experiences on university graduates’ vocational self-concept

Abstract: Purpose – The purpose of this paper is to assess the relative effects of participation in cooperative education (co-op) and engagement in reflection upon previous work experiences on undergraduate students’ vocational self-concept (VSC) at graduation. Design/methodology/approach – A cross-sectional survey of graduating students (n=1,483) from a Canadian university was used. Regression models and a mediation analysis were used to test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 44 publications
0
20
0
4
Order By: Relevance
“…The location of the study (a university in southwestern Ontario) is unique in terms of the breadth of cooperative education, though many colleges and universities across Canada include work placements or internships in undergraduate and graduate degree curricula (Rodriguez, Zhao, & Ferguson, 2016). Co-op programs have been found to enhance self-efficacy and confidence and contribute to student retention (Drewery, Nevison, & Pretti, 2016;Newhook, 2016). However, although our sample is small, students expressed that uncertainty regarding co-op income and expenses exacerbated financial instability.…”
Section: Discussionmentioning
confidence: 99%
“…The location of the study (a university in southwestern Ontario) is unique in terms of the breadth of cooperative education, though many colleges and universities across Canada include work placements or internships in undergraduate and graduate degree curricula (Rodriguez, Zhao, & Ferguson, 2016). Co-op programs have been found to enhance self-efficacy and confidence and contribute to student retention (Drewery, Nevison, & Pretti, 2016;Newhook, 2016). However, although our sample is small, students expressed that uncertainty regarding co-op income and expenses exacerbated financial instability.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, WIL and internship curriculum-based programs have been well documented in helping students develop clear expectations of industry work, soft-skill development, networking and building students' general confidence (Elijido & Kloot, 2015;Drewery et al, 2016;Jackson, 2017). Along with studying specific outcomes of curriculum-based experiences (i.e.…”
Section: Background Literaturementioning
confidence: 99%
“…While there was mention of structured, curriculum-based WIL and placement experiences within the literature (e.g. Elijido & Kloot, 2015;Drewery et al, 2016;Jackson, 2017), findings indicated any type of work experience, including volunteering, was key in preparing to transition to professional work.…”
Section: Theme 1 -Soft-skills and Work Experiencementioning
confidence: 99%
“…As such, the transformation a student's experience may be facilitated by opportunities to reflect on the impact of an internship on occupational choices. The positive connection between an internship and enhanced vocational selfconcept has been reported as further evidence that reflecting on work experience better prepares students for the career industry (Drewery, Nevison, & Pretti, 2016). Stichman and Farkas (2005) conducted a nationwide study on internships in undergraduate criminal justice programs and found the major strength of an internship to be the student's' ability to integrate theory and practice.…”
Section: Internshipsmentioning
confidence: 97%
“…Research supports the value that internships hold in helping students become aware of their vocational attributes. (Taylor, 1988;Drewery et al, 2016).…”
Section: Career-orientedmentioning
confidence: 99%